Groundwater optimization handbook flow, contaminant transport, and conjunctive management - Peralta, Richard C. (CRC Press, 2012)
"Book overview Existing and impending water shortages compel improved water quantity and quality management. The handbook demonstrates : - true optimization of groundwater and conjunctive water management; - real-world design procedures, as opposed to academic exercises; - how to lead client, agency and consultant personnel through the strategy design and adaptation process; - a realistic approach to complex problems for individuals with varying levels of familiarity with groundwater hydrology and mathematical optimization; - how to formulate common situations as clear deterministic or stochastic mathematical optimization problems;"-- Provided by publisher.
Keywords: Groundwater -- Pollution.; Groundwater flow.; Water quality management.; elektronické knihy; electronic books